Pulsatilla decoction alleviates DSS-induced UC by activating FXR-ASBT pathways to ameliorate disordered bile acids homeostasis - Xiao, Ying; Jia, Ya-qian; Liu, Wen-juan; Niu, Chun; Mai, Zhan-hai; Dong, Jia-qi; Zhang, Xiao-song; Yuan, Zi-wen; Ji, Peng; Wei, Yan-ming; Hua, Yong-li (Frontiers in Pharmacology, 2024)
Ethnopharmacological relevance Pulsatilla decoction (PD) is a classical prescription for the treatment of ulcerative colitis. Previous studies have demonstrated that the therapeutic efficacy of PD is closely associated with the activation of Farnesoid X receptor (FXR). The activity of FXR is regulated by apical sodium-dependent bile acid transporter (ASBT), and the FXR-ASBT cascade reaction, centered around bile acid receptor FXR, plays a pivotal role in maintaining bile acid metabolic homeostasis to prevent the occurrence and progression of ulcerative colitis (UC).To elucidate the underlying mechanism by which PD exerts its prote active effects against Dextran Sulfate Sodium Salt (DSS)-induced ulcerative colitis, focus ing on the modulation of FXR and ASBT.To establish a model of acute ulcerative colitis, BALB/C mice were administered 3.5% DSS in their drinking water for consecutive 7 days. The disease activity index (DAI) was employed to evaluate the clinical symptoms exhibited by each group of mice. Goblet cell expression in colon tissue was assessed using glycogen schiff periodic acid shiff (PAS) and alcian blue staining techniques. Inflammatory cytokine expression in serum and colonic tissues was examined through enzyme-linked immunosorbent assay (ELISA). A PCR Array chip was utilized to screen 88 differential genes associated with the FXR-ASBT pathway in UC treatment with PD. Western blotting (WB) analysis was performed to detect protein expression levels of differentially expressed genes in mouse colon tissue.The PD treatment effectively reduced the Disease Activity Index (DAI) score and mitigated colon histopathological damage, while also restoring weight and colon length. Furthermore, it significantly alleviated the severity of ulcerative colitis (UC), regulated inflammation, modulated goblet cell numbers, and restored bile acid balance.3 Additionally, a PCR Array analysis identified 21 differentially expressed genes involved in the FXR-ASBT pathway. Western blot results demonstrated significant restoration of FXR, GPBAR1, CYP7A1, and FGF15 protein expression levels following PD treatment; moreover, there was an observed tendency towards increased expression levels of ABCB11 and RXRα.The therapeutic efficacy of PD in UC mice is notable, potentially attributed to its modulation of bile acid homeostasis, enhancement of gut barrier function, and attenuation of intestinal inflammation.